4

: NPN-equivalence : ,f ,g :NPN equivalent ,f f,g ( ( )f ) . .1 .2 .3

:NPN . .class . . , . . , , . . .

: "

.1

:

F = ab c + abd + bc d
. (negation)

?

"

(15%) (

ϕ1 = xyz + x yv + yz v ϕ2 = xy + xv + zv + zy

ϕ3 = xv + zv + zy + x v
ϕ4 = yzv + x zv + xyzv + x y zv
:

? -

"

(15%) (

ϕ1 = xyz + x yv + yz v
-

ϕ2 = xy + xv + zv + zy ,
ϕ3 = xv + zv + zy + x v

-

ϕ4 = yzv + x zv + xyzv + x y zv
, ( 1, 2, 3, 4 ) (10%) (

( x, y, z,v )
.

ϕ2 = x y + xv + zv + zy
1) 2)

y

ϕ2 ϕ2

z

x
y

ϕ2

x

z

v

ϕ2

ϕ 4 = yzv + x zv + xyz v + x y z v =
= yzv + xyz + x y v
1) 2)

z
x
y

ϕ4 ϕ4

y

ϕ4

x
z
:

ϕ4

: ) F ( x1 , Y ) ≥ F ( x2 , Y )

x1 > x2

,X

.( F (1, Y ) ≥ F (0, Y )

:

x1 > x2

,X : ) F ( x1 , Y ) ≤ F ( x2 , Y )

.( F (1, Y ) ≤ F (0, Y )

,X . . . : . : SOP . . : ( )? . .

f1 = x1 x3 + x1 x2
:

x1 − nonmonoton x2 − antiton x3 − isoton f1 − nonmonton

f 2 = x1 x2 x3 + x2 x4 x1 − iso x2 − antit x3 − iso x4 − antit f 2 − monot

f 3 = x1 x2 x3 + x1 x2 x4 + x1 x4
( )

f 3 = x1 x2 x3 + x1 x2 x4 + x1 x4 = x1 x2 x3 + x1 x2 + x1 x4 = x2 x3 + x1 x2 + x1 x4
.

.

22

:

2 2 = 16
0 1 Mono, iso,anti Mono, iso,anti

x y x' y' xy x+y x'y' x'+y' xy' x'y x'+y x+y' x'y+xy' xy+x'y'

iso iso anti anti iso iso anti anti mono mono mono mono nonmono nonmono

.

2-

14 "

:

:

F ( X ) = G( X )

G( X )

F(X ) F(X )
: -

F(X ) = F(X )

( x + y) ' = x ' y ' ( xy ) ' = x '+ y '
: :

f1 = x1 x2 + x1 x3

f1d = x1 x2 + x1 x3 = x1 x2 & x1 x3 = ( x1 + x2 )( x1 + x3 ) = x1 + x1 x2 + x1 x3 + x2 x3 = x1 + x2 x3

: (! .0

(1- 0 )0

), 1 1 : , , .1 .2

0 →1 1→ 0 +→• •→+
: . . .! ? n2-( ) x, y, x ', y '

22

( n−1)

NPN class :

f1 = x1 ' x2 + x2 x3 '+ x1 ' x3 '
f1d = ( x1 '+ x2 )( x2 + x3 ')( x1 '+ x3 ') = ( x1 ' x2 + x1 ' x3 '+ x2 + x2 x3 ')( x1 '+ x3 ') = x1 ' x2 + x1 ' x2 x3 '+ x1 ' x3 '+ x1 ' x3 '+ x2 x1 '+ x2 x3 '+ x2 x3 ' x1 '+ x2 x3 ' = x1 ' x2 + x1 ' x3 '+ x2 x3 '

f 2 = abc + abd + bcd + acd + acd = ac + ab + ad + bcd

f 2 d = (a + c)(a + b)(a + d )(b + c + d ) = (a + bc)(d + a (b + c)) = = (a + bc)(d + ab + ac) = ad + ab + ac + bcd + abc + abc = ad + ab + ac + bcd

.

f 3 = abc + bd '+ a ' b ' d + bc
f 3d = (a + b + c)(b + d ')(a '+ b '+ d )(b + c) = (b + d '(a + c))(a ' b + a ' c + b ' c + db + dc) = (b + ad '+ cd ')(a ' b + a ' c + db + dc) = a ' b + a ' bc + db + bdc + cda ' b + a ' cd ' = a ' b + db + cda ' b + a ' cd ' ≠ f3

. :(2 : ) 3NPN

F1 ( x1 , x2 , x3 ) = x1 x2 + x2 x3 + x1 x3 (majority ) F2 ( x1 , x2 , x3 ) = x1 ⊕ x2 ⊕ x3 ( xor )

F(X ) = F(X )

anti-self-dual

:

?anti –self-dual

f1 = a ⊕ b = ab '+ a ' b f1 ( x) = a ' b ''+ a '' b ' = a ' b + ab ' = f1

.ASD

f2 = a + b f 2 ( x) = a '+ b ' ≠ f 2
.ASD

n+1

self-dual

F(Y)

n

non-self-dual :

: F(x,Y)

F ( x, Y ) = xF (Y ) + x f d (Y )

: :

xi , x j F ( xi , x j , Y ) = F ( x j , xi , Y )
,

) .(

: ? .

f1 = xy ' z '+ x ' yz '+ x ' y ' z

f 2 = xy '+ z
: . . . work number 1 work number n+1 .1 kn work number :

n wn , . f1

S

n k

. . : . . -, ,S
n k 3 xyz '+ xy ' z + x ' yz + xyz = S 2 + S33

.

?

f = x + y + x'z f = x + y + x ' z = x( yz + y ' z + yz '+ y ' z ') + y ( xz + x ' z + xz '+ x ' z ') + x ' z ( y + y ') =

xyz + xy ' z + xyz '+ xy ' z '+ xyz + x ' yz + xyz ' + x ' yz '+ x ' zy + x ' y ' z = xyz + xy ' z + xyz ' + xy ' z ' + x ' yz + x ' yz ' + x ' y ' z =
3 = S33 + S13 + S2

.

?

f = xy f = xy ( z + z ') = xyz + xyz '
, .